2020
DOI: 10.1177/0886260520909186
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Sextortion: An Exploratory Analysis of Different Perpetrators Engaging in a Similar Crime

Abstract: Sextortion, a portmanteau of “sexual” and “extortion,” is the threat to distribute intimate, sexual materials unless a victim complies with certain demands. Cyber sextortion is part of a larger continuum of image-based sexual offending in which images are used for harm. Despite the serious nature of this crime, there exists a dearth of empirical knowledge of sextortion. This article employed a qualitative content analysis of media articles and court documents to explore the crimes of 152 cyber sextortion offen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
0
45
0
1
Order By: Relevance
“…Image-based sexual abuse (IBSA) is an increasingly criminalized form of technology-facilitated abuse, one that includes creating, distributing, or threatening to distribute intimate (nude or sexual) photos or videos of someone without their consent (DeKeseredy & Schwartz, 2016; Henry et al, 2021; McGlynn & Rackley, 2017). Perpetration of IBSA-related behaviors is referred to with other distinct terminology across the literature, including “non-consensual sexting” (Barrense-Dias et al, 2020), “non-consensual sext dissemination” (Clancy et al, 2019), “non-consensual image sharing” (Naezer & van Oosterhout, 2020), “cyber sextortion” (O’Malley & Holt, 2020), and “technology-based sexual coercion” (Thompson & Morrison, 2013). Regardless of terminology, most existing IBSA studies focus squarely on the non-consensual distribution of intimate images, whether posting online or sending directly onto others (as we discuss further below), rather than including the three forms of IBSA perpetration that are increasingly criminalized in jurisdictions across the globe (e.g., Abusive Behaviour and Sexual Harm (Scotland) Act 2016; Criminal Justice and Courts Act 2015 (UK) ; Enhancing Online Safety Act 2015 (Cth); and Harmful Digital Communications Act 2015 (NZ)).…”
Section: Introductionmentioning
confidence: 99%
“…Image-based sexual abuse (IBSA) is an increasingly criminalized form of technology-facilitated abuse, one that includes creating, distributing, or threatening to distribute intimate (nude or sexual) photos or videos of someone without their consent (DeKeseredy & Schwartz, 2016; Henry et al, 2021; McGlynn & Rackley, 2017). Perpetration of IBSA-related behaviors is referred to with other distinct terminology across the literature, including “non-consensual sexting” (Barrense-Dias et al, 2020), “non-consensual sext dissemination” (Clancy et al, 2019), “non-consensual image sharing” (Naezer & van Oosterhout, 2020), “cyber sextortion” (O’Malley & Holt, 2020), and “technology-based sexual coercion” (Thompson & Morrison, 2013). Regardless of terminology, most existing IBSA studies focus squarely on the non-consensual distribution of intimate images, whether posting online or sending directly onto others (as we discuss further below), rather than including the three forms of IBSA perpetration that are increasingly criminalized in jurisdictions across the globe (e.g., Abusive Behaviour and Sexual Harm (Scotland) Act 2016; Criminal Justice and Courts Act 2015 (UK) ; Enhancing Online Safety Act 2015 (Cth); and Harmful Digital Communications Act 2015 (NZ)).…”
Section: Introductionmentioning
confidence: 99%
“…39 A recent exploratory study of data related to 152 cyber-extortion offenders (where there were demands for victims to produce more sexually explicit images and threats to distribute self-produced sexual images of minors if they refused or attempted to end contact with the offender) found that the majority of cases focused on extorting minors (52.6 per cent). 40 From a victim perspective, the consequences of aggravated sexting or sextortion are considerable and have been linked for some young people to depression, self-harm, and other forms of psychopathology. 41,42 Concerns about the creation of content by exploited young people was also discussed in two earlier publications by the UK Charity Barnardos.…”
Section: Why Is This Important?mentioning
confidence: 99%
“…50 Another challenge facing the legal system is that sexting by young people is positioned as intersecting among a variety of legal rights, such as privacy, free speech 39 Quayle et al [46]. 40 [40]. 41 Wachs et al [59].…”
Section: Why Is This Important?mentioning
confidence: 99%
“…"Sextortion" is the practice of extorting money, sex, or other favors by threatening the victims to share their intimate photo, audio, text, video, or other media on the Internet or with closed social groups. 1 There are several definitions of sextortion available on online dictionaries. Some of them are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%